Global Robust Control Model of Friction Stir Welding of Aluminum Alloy Based on Main Motor Power Output Prediction - Kun Zhang; Zhengjun Liu (IEEE Access, 2019)
Aiming at the softening problem of 7075 superhard aluminium welded joints such as hot cracks and gas holes in traditional fusion welding process, a dynamic robust control model based on the relationship between friction stir welding process parameters and welded joint strength is established. According to the non-linear relationship between global motion estimation and welded strength parameters, a dynamic robust control model of stirring needle motion is established, and the physical parameters such as elongation after fracture, tensile strength and hardness are calculated. A robust dynamic evolutionary optimization model of welding process parameters is established in the future to realize real-time optimization control of process parameters. On the basis of global motion control, the electric power output of the friction stir welding main motor is predicted according to the required line energy input of the stirring needle motion characteristics, and the real-time optimal control method of the motor electric power based on the expected thermal energy input of the welding process is established. A series of strength tests of welded joints based on the model show that the predicted results of the model can meet the needs of engineering and have practical value in engineering.